2010
DOI: 10.1159/000264791
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Coblation Decreases Blood Loss during Endoscopic Sinonasal and Skull Base Tumor Removal

Abstract: Background/Aims: Minimizing bleeding during transnasal resections of sinonasal tumors is imperative for optimizing visualization and decreasing complications. The purpose of the present study was to determine whether radiofrequency coblation decreases blood loss during endoscopic tumor removal. Methods: Sinonasal/skull base tumors treated in 2008 with endoscopic techniques were reviewed. The data collected included demographics, histopathology, technique, duration, complications and estimated blood loss (EBL).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…It can be performed with minimal morbidity and low intraoperative blood loss, even with nonembolized tumors up to Radkowski IIC. Given these cases and other experiences using the coblator in endoscopic sinus and skull base surgery [14], this device has become an important option in the armamentarium to JNA tumor removal using minimally invasive coblation assisted techniques.…”
Section: Resultsmentioning
confidence: 99%
“…It can be performed with minimal morbidity and low intraoperative blood loss, even with nonembolized tumors up to Radkowski IIC. Given these cases and other experiences using the coblator in endoscopic sinus and skull base surgery [14], this device has become an important option in the armamentarium to JNA tumor removal using minimally invasive coblation assisted techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Low-temperature plasma radiofrequency is a minimally invasive treatment for nasal inverted papilloma. Endoscopic surgery using the low-temperature plasma radiofrequency had the following advantages: less blood loss, complete en bloc tumour resection, mild injury, short surgery time, and mild postoperative pain [413, 414]. …”
Section: Treatmentmentioning
confidence: 99%
“…As a consequence, it generates much less thermal energy and is less likely to cause thermal collateral damage. A recent pilot study demonstrated decreased blood loss with the use of the Coblator compared with the microdebrider [49] for polyp resection and a similar study has shown similar results with sinonasal and skull base tumor resections [50].…”
Section: Surgical Techniquementioning
confidence: 79%